2014
DOI: 10.1007/s10578-014-0489-8
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating and its Association with Overweight and Health-Related Quality of Life Among Adolescents in Selected High Schools of Tehran

Abstract: This study aimed to determine the association between disordered eating and overweight and also health-related quality of life (HRQOL) among adolescents in high schools of Tehran. The participants were 465 adolescents, aged 14-17 years. After anthropometric measurements, body mass index-for-age and body weight status were determined using World Health Organization cut offs. The Eating Attitudes Test-26 (EAT-26) and Pediatric Quality of Life Inventory (PedsQL™4.0) were used to assess disordered eating and HRQOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 37 publications
0
36
2
Order By: Relevance
“…This is in accordance with Musaiger et al who found a two to three times higher risk for DE among overweight/obese compared to non-overweight/obese boys and girls in seven Arab countries [ 40 ]. Corresponding values have also been found among Mexican adolescents [ 41 ] and among adolescents in high schools in Tehran [ 39 ]. Neumark-Sztainer et al [ 68 ] found that American overweight adolescents report being teased about their weight and being bothered by the teasing, and further that weight-teasing is associated with DE behaviors that may place overweight youth at increased risk for weight.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This is in accordance with Musaiger et al who found a two to three times higher risk for DE among overweight/obese compared to non-overweight/obese boys and girls in seven Arab countries [ 40 ]. Corresponding values have also been found among Mexican adolescents [ 41 ] and among adolescents in high schools in Tehran [ 39 ]. Neumark-Sztainer et al [ 68 ] found that American overweight adolescents report being teased about their weight and being bothered by the teasing, and further that weight-teasing is associated with DE behaviors that may place overweight youth at increased risk for weight.…”
Section: Discussionmentioning
confidence: 52%
“…Some studies have shown a higher prevalence and/or a higher risk of DE among overweight or obese adolescents compared to normal weight adolescents [ 39 42 ]. These studies, however, have only used one screening instrument to define DE, thereby increasing the risk for false negative subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Jalali‐Farahani et al () studied disordered eating by Eating Attitudes Test‐26 (EAT‐26) among 465 adolescents 14 to 16 years old in high schools of Tehran (Jalali‐Farahani et al, ). The prevalence of disordered eating was 26.4% among girls and 11.8% among boys.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed on a regional scale in Iran to estimate the prevalence of eating disorders. Most of these studies were school-based (Nobakht & Dezhkam, 2000) or these studies were conducted among specific populations, such as university dormitories or fitness centers (Khabir, Sajjadi, & Aflakseir, 2016), and specific genders (mostly girls) (Jalali-Farahani, Chin, Mohd Nasir, & Amiri, 2015) or among adult populations (Khabir et al, 2016). Additionally, most of them were limited to local populations, and they were not generalizable to the country.…”
Section: Introductionmentioning
confidence: 99%
“…HrQoL was also intensively studied in the context of overweight and obesity showing that HrQoL is especially reduced in overweight and obese adolescents (Doyle, Grange, Goldschmidt, & Wilfley, ; Latzer & Stein, ). To date, only a few studies investigated the association between disordered eating as assessed by the SCOFF and other questionnaires and HrQoL in large population samples of adolescents (Herpertz‐Dahlmann et al, ; Jalali‐Farahani, Chin, Nasir, & Amiri, ), demonstrating a decreased HrQoL in adolescents with disordered eating behaviours. Herpertz‐Dahlmann et al () observed a general association between the SCOFF score and HrQoL, but they did not analyse if there are distinct eating behaviours that are more associated with a decline in HrQoL than others.…”
Section: Introductionmentioning
confidence: 99%